Legal Reconstruction of Subsidized Products from the Perspective of Consumer Protection - Yatini, Yatini; Safitri, Wahyuni; Pratiwie, Dinny Wirawan; Sari, Mieke Yustia Ayu Ratna; Rustiana, Rustiana (LPPM Institut Pendidikan Nusantara Global, 2025)
The Consumer Protection Law in Indonesia has so far focused more on transactions between consumers and business actors without distinguishing between commercial products and subsidized products . In fact, subsidized products such as clean water from PDAM, subsidized electricity, and subsidized fuel have different legal characteristics because The price is set by the government and monitored by certain bodies . This difference has implications for price transparency, service quality standards, and dispute resolution mechanisms which is not fully regulated in the UUPK. This article aims to analyze the incompleteness of consumer protection regulations for subsidized products and propose a fairer and more effective legal reconstruction . By using normative approach , this research to study national regulations, WTO principles related to subsidies, and comparative studies with other countries . The results of the study indicate that consumer protection for subsidized products requires a more specific legal framework. to guarantee consumer rights without ignoring the interests of the government as a regulator and service provider as a special business actor . Therefore, it is necessary regulatory reconstruction that accommodates price transparency, improved service quality, and clearer dispute resolution mechanisms for consumers of subsidized products